Physiological of Various Genotypes of Cayenne pepper (Capsicum frutescens L.) Under Heat Stress - Nanda, Riri Fitria; Adiwirman, Adiwirman; Herman, Herman (Photon: Jurnal Sain dan Kesehatan, 2025)
Cayenne pepper (Capsicum frutescens L.), a member of the Solanaceae family, is vulnerable to rising temperatures caused by global warming, which may reduce productivity and impair plant growth. This study evaluated the adaptation of four cayenne pepper genotypes (Pelita, Dewata, Bara, and Taruna) to high-temperature stress under greenhouse conditions. A split-plot design was applied, with temperature regimes as the main plot, consisting of normal daily temperature and heat stress conditions (±4°C–8°C above normal temperature), while genotypes were assigned as sub-plots. Observed parameters included physiological traits, such as stomatal conductance and transpiration rate, and morphological traits, including plant height, stem diameter, flowering time, harvesting age, and fruit weight. Data were analysed using ANOVA followed by a 5% significance test. The results demonstrated that high-temperature stress significantly affected both physiological and morphological characteristics of cayenne pepper plants. Temperature stress generally reduced fruit weight compared with normal daily temperature conditions. Responses to heat stress were observed in stomatal conductance, transpiration rate, plant height, stem diameter, leaf morphology, flowering age, harvest age, and fruit yield. Among the tested genotypes, Taruna exhibited superior physiological adaptation through stable stomatal conductance, chlorophyll content, photosynthetic activity, and leaf morphology under stress conditions. However, the Dewata genotype produced the highest fruit weight per plant under elevated temperature conditions compared with Pelita, Bara, and Taruna. These findings provide valuable insights for developing cayenne pepper varieties adaptive to climate change, with emphasis on physiological stability and yield performance as key selection criteria.